2006
DOI: 10.1007/s00266-004-5026-x
|View full text |Cite
|
Sign up to set email alerts
|

Intraabdominal Pressure in Abdominoplasty Patients

Abstract: Abdominal compartment syndrome is directly related to an increase in intraabdominal pressure (IAP), which can lead in severe cases to serious clinical consequences. Routine measurement of IAP in specific cases has been advocated by some surgical specialties. However, few studies in plastic surgery have focused on the use of IAP. The authors review the literature and describe a method of IAP analysis used for 12 patients who underwent abdominoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 16 publications
0
17
1
1
Order By: Relevance
“…[22] The operative technique has at least two maneuvers that result in IAP elevation: plication of the rectus muscle and flap resection. [23] In this study, we found no change in respiratory dynamics regardless the type of ventilatory mode in response to change in IAP after plication of the rectus muscle.…”
Section: Discussioncontrasting
confidence: 44%
“…[22] The operative technique has at least two maneuvers that result in IAP elevation: plication of the rectus muscle and flap resection. [23] In this study, we found no change in respiratory dynamics regardless the type of ventilatory mode in response to change in IAP after plication of the rectus muscle.…”
Section: Discussioncontrasting
confidence: 44%
“…The mean age of patients in group A was 37.2 ±4.5 years, range (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). In group B was 38.7± 3.2 years, range (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The mean Body Mass Index (BMI) of patients in Group A was 28.9±1.8, range (27.5-29.8), range.…”
Section: Resultsmentioning
confidence: 99%
“…Neto et al, [30] performed analysis of postoperative intraabdominal pressure after abdominoplasty. All subjects of their study were healthy female with ages varying from 28 to 47 years old, which is similar group of patients like in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the increase of intraabdominal pressure caused by different maneuvers used to correct myoaponeurotic laxity, [9][10][11] there is also the effect of abdominal flap traction, which can be transferred to the abdominal cavity. [13][14][15] In 1996, Matarasso brought to light the hypothesis that the use of compression garments could be one of the reasons for the increase of intraabdominal pressure, thus generating a higher incidence of deep venous thrombosis and pulmonary embolism after abdominoplasty. Some authors have measured the intraabdominal pressure by using an intravesical catheter and have stated that it does increase during the early postoperative period.…”
mentioning
confidence: 99%